Versatility provided by electrostatic torsional microstructure as consequence of its complex dynamics. Issue 4 (1st February 2014) - Scerri, J.; Grech, I.; Gatt, E.; Casha, O.
Abstract : The results presented show that a simple microstructure involving a plate supported by two tethers can exhibit varied dynamics due to its nonlinearities. The plate vibrates such that the tethers experience a torsional twisting and it is designed within the constraints imposed by the MetalMUMPs process. Each region of operation has different applications and one can traverse through these regions by adjusting the sensing and actuation voltages. As one would expect, the nonlinearities dominate at higher voltages, with the first signs of chaotic trajectories appearing at 75 V. Parameters of the nonlinear model are first determined from finite‐element analysis responses, and results from subsequent numerical simulations for each region are presented.